2013
DOI: 10.1080/ac.68.3.2983421
|View full text |Cite
|
Sign up to set email alerts
|

Effi cacy of papillary muscle approximation in preventing functional mitral regurgitation recurrence in high-risk patients with ischaemic cardiomyopathy and mitral regurgitation

Abstract: iPMD is a valuable index in the riskstratification of the recurrence of post-MAP MR in patients with DCM complicated by FMR.The patients treated with MAP plus PMA had more favourable outcomes and lower recurrence rates than those treated via the traditional route of MAP only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
3
22
0
1
Order By: Relevance
“…At five‐year follow‐up, the use of a Ring+Sling was associated with a smaller left ventricular end‐diastolic diameter (57 mm vs. 61 mm; p = 0.001) and greater ejection fraction (44% vs. 40%; p < 0.001), a lower prevalence of moderate or greater recurrent MR (27% vs. 56%; p = 0.01), and similar survival (77% vs. 71%; p = 0.71), as compared with a Ring only. Previous retrospective studies have reported the mid‐term prevalence of recurrent moderate or greater MR as 3.4–6% after a Ring+Sling, with a cumulative survival of approximately 80% . The present study adds to this published data, and supports the use of a Ring+Sling for both ischemic and non‐ischemic cardiomyopathy, as well as its application through a right thoracotomy approach.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…At five‐year follow‐up, the use of a Ring+Sling was associated with a smaller left ventricular end‐diastolic diameter (57 mm vs. 61 mm; p = 0.001) and greater ejection fraction (44% vs. 40%; p < 0.001), a lower prevalence of moderate or greater recurrent MR (27% vs. 56%; p = 0.01), and similar survival (77% vs. 71%; p = 0.71), as compared with a Ring only. Previous retrospective studies have reported the mid‐term prevalence of recurrent moderate or greater MR as 3.4–6% after a Ring+Sling, with a cumulative survival of approximately 80% . The present study adds to this published data, and supports the use of a Ring+Sling for both ischemic and non‐ischemic cardiomyopathy, as well as its application through a right thoracotomy approach.…”
Section: Discussionsupporting
confidence: 75%
“…To address the subvalvular dysfunction in secondary MR, several surgical techniques have been proposed to complement a conventional Ring repair, including papillary muscle approximation via a papillary muscle sling placement (Ring+Sling) . The reported benefits of a Ring+Sling include a sustained reduction in MR, decreased leaflet tethering, result in reverse left ventricular remodeling, and improved functional status . In the present study, we evaluated the safety and efficacy of a Ring+Sling in patients with moderate‐to‐severe secondary MR, and compared their results in a propensity‐matched analysis with patients undergoing isolated Ring repair.…”
Section: Introductionmentioning
confidence: 99%
“…The search protocol yielded 392 studies, of which seven satisfied the inclusion criteria and were included in the quantitative analysis (Fig. ) . All of the included studies were retrospective or propensity‐matched analyses, and consisted of 531 total patients.…”
Section: Resultsmentioning
confidence: 99%
“…For papillary muscle relocation procedures, the posterior papillary muscle was relocated toward the anterior mitral annulus utilizing polytetrafluoroethylene sutures from the papillary muscle head through the aorto‐mitral continuity in one study, bilateral papillary muscle relocation to the ipsilateral annulus was performed in a second study, and bilateral papillary muscle relocation to either the anterior or posterior annulus was performed in a third study . Finally, for papillary muscle approximation, a 4‐mm polytetrafluoroethylene tube or umbilical tape was used to encircle and approximate the papillary muscles …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation